Development and evaluation of the psychometric properties of the Adolescent Motor Competence Questionnaire (AMCQ) for Adolescents. (December 2016) - Timler, Amanda; McIntyre, Fleur; Cantell, Marja; Crawford, Susan; Hands, Beth
Abstract: Background: There are no valid and reliable self-report measures designed to identify level of motor competence and suspected motor difficulties among 12–18 year old adolescents. Aim: This paper reports the development and evaluation of a self-report questionnaire (Adolescent Motor Competence Questionnaire; AMCQ) to address this need. Method: The project proceeded in 3 phases; (A) item development, (B) content evaluation, and (C) examination of reliability and validity of the final questionnaire. Each phase was informed by criteria A and B in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), comments from a sample of 10 adolescents aged between 12 and 18 years with a range of movement skills, key informants and international experts. A convenience sample of 38 adolescents completed the final version of the AMCQ. The McCarron Assessment of Neuromuscular Development (MAND) was used to investigate concurrent validity. Results: The final version of the AMCQ comprised 26 items scored using a 4 point Likert scale with a maximum score of 104. Analyses revealed the questionnaire has an acceptable internal consistency (0.902) and 7 day test-retest reliability (0.956). A moderate positive correlation between the AMCQ and the MAND of 0.491 ( p < 0.002) provides some evidence of concurrent validity. Conclusion: The development of the AMCQ was exploratory in nature and has the potential to be a reliable and valid tool for measuring motor competence in Australian adolescents.